Ice cover and thermal regime in a dimictic seepage lake under climate change. Issue 3 (3rd July 2018) - Hamilton, David P.; Magee, Madeline R.; Wu, Chin H.; Kratz, Timothy K.
ABSTRACT: Changes in water temperature and ice cover are important for controlling the biogeochemical and food-web processes of dimictic lakes in temperate regions. To investigate these changes, we applied a 1-dimensional hydrodynamic lake-ice model to Crystal Lake, a 20 m deep, dimictic seepage lake in northern Wisconsin, USA, to a period of 23 years (1989–2011). The model, DYRESM-WQ-I, incorporates the evolution of blue ice, white ice, and snow cover; time-varying ice and snow albedo; and 2-way coupling across the ice–water interface by incorporating components of previous ice models embedded in the hydrodynamic component of the DYRESM-WQ model. A new element of the current model is time-varying sediment heat fluxes, important to under-ice water temperatures in shallow lakes. Simulations closely reproduce the observed annual stratification regime and ice phenology with standard errors in temperature of 0.7 °C; total difference of 10–20% in ice thickness compared with measured values; and standard errors of 0.9 d for ice-on and 1.55 d for ice-off. Under a likely future climate scenario involving changes in air temperature forecasted to occur by the middle of this century (2055), results suggest an average reduction in mean ice cover thickness of about 0.18 m and an increase in surface mixed-layer temperature of up to 3.5 °C over summer. In addition, water levels decreased by 5.1 m over the simulation period, mostly in response to greater evaporation from higher surface water temperature in summer. The results have important implications for seepage lakes in temperate regions, where projected changes in precipitation with climate warming will not compensate for increased evaporation from the lake surface and the likely alteration in groundwater flows.